2022
DOI: 10.1021/acs.joc.2c01895
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Synthesis of SynVesT-1, a Synaptic Density Positron Emission Tomography Imaging Agent

Abstract: Heterocyclic nonacetamide ligands are used as positron emission tomography (PET) imaging agents of the synaptic vesicle glycoprotein 2A (SV2A), with potential applications in the diagnosis of various neuropsychiatric diseases. To date, the main synthetic strategy to access these optically active compounds has involved the racemic synthesis of a late-stage intermediate followed by the separation of the enantiomers. Here, we describe the use of iminium organocatalysis for the asymmetric synthesis of SynVesT-1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…16,17 [ 18 F]SynVesT-1 is a PET tracer recently developed for SV2A and has been used in human studies. [18][19][20] Previous research has shown reductions of SV2A binding in the hippocampal region of patients with TLE compared to healthy controls. 21 These studies emphasized regional SV2A uptake changes or quantified predefined abnormal regions in PET images, but without comprehensively considering the role of cognitive co-morbidities in synaptic loss.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 [ 18 F]SynVesT-1 is a PET tracer recently developed for SV2A and has been used in human studies. [18][19][20] Previous research has shown reductions of SV2A binding in the hippocampal region of patients with TLE compared to healthy controls. 21 These studies emphasized regional SV2A uptake changes or quantified predefined abnormal regions in PET images, but without comprehensively considering the role of cognitive co-morbidities in synaptic loss.…”
mentioning
confidence: 99%
“…SV2A, expressed in almost all synapses and located within the synaptic vesicles at presynaptic terminals, 15 serves as the binding site for the antiseizure medication (ASM) levetiracetam (LEV) 16,17 . [ 18 F]SynVesT‐1 is a PET tracer recently developed for SV2A and has been used in human studies 18–20 . Previous research has shown reductions of SV2A binding in the hippocampal region of patients with TLE compared to healthy controls 21 .…”
mentioning
confidence: 99%